2022
DOI: 10.21608/aimj.2022.100728.1603
|View full text |Cite
|
Sign up to set email alerts
|

Two Dimensional and Color Doppler Ultrasound Scoring in Evaluation of Anterior Low Lying Placenta and its Adherence to Previous One Cesarean Section Scar inthe Third Trimester

Abstract: Users have the right to read, download, copy, distribute, print, search, or link to the full texts of articles under the following conditions: Creative Commons Attribution-Share Alike 4.0 International Public License (CC BY-SA 4.0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The findings related to this study declared that the incidence of acreta in the risk groups was 52.0%, in agreement with our results reported that Placenta accreta is much more common than placenta increta and percreta with the succeeding incidences: placenta accreta -79%; placenta increta -14%; and placenta percreta 7%. 14 Regarding our results in the percent of acreata (52.0%), it was found that Mohammed et al,study was agreement with our results, they found that placenta accreta was more common than increta and percreta. Abnormal placentation: 50.8% (32 cases) placenta accreta; 34.9% (22 cases) placenta increta; and 14.3% (9 cases) placenta percreta.…”
Section: Discussionsupporting
confidence: 92%
“…The findings related to this study declared that the incidence of acreta in the risk groups was 52.0%, in agreement with our results reported that Placenta accreta is much more common than placenta increta and percreta with the succeeding incidences: placenta accreta -79%; placenta increta -14%; and placenta percreta 7%. 14 Regarding our results in the percent of acreata (52.0%), it was found that Mohammed et al,study was agreement with our results, they found that placenta accreta was more common than increta and percreta. Abnormal placentation: 50.8% (32 cases) placenta accreta; 34.9% (22 cases) placenta increta; and 14.3% (9 cases) placenta percreta.…”
Section: Discussionsupporting
confidence: 92%